OBSESSIVE-COMPULSIVE BEHAVIOR IN ELEMENTARY AGED CHILDREN - Webb, Ida (Acta Scientiae et Intellectus, 2024)
This paper focuses primarily on Obsessive Compulsive Behavior (OCD) among elementary school children. The purpose of this paper is to determine the effects of OCD on children below the age of ten years and establish how these effects may impact their lives both in childhood and adulthood. The paper starts by focusing on a definition of the condition with the aim of differentiating it from other related mental health issues. Following the definition in the introduction, the paper analyses the signs and symptoms associated with OCD. This segment is followed by the impacts of the condition on elementary school children and the conclusive remarks focus on steps that can be taken to improve the school environment for children with OCD aged below ten years.